Concepts of humanistic theory in obstetric care - Isolda Pereira da Silveira; Ana Fátima Carvalho Fernandes (Rev Rene)
This study reflects the concepts of Paterson’s and Zderad’s humanistic theory, applied to daily nursing care during labor and childbirth. The objective of the study is to understand the importance of their application to attendant care. We take into account that the application of such concepts in obstetric nursing provides to the nurse and the expectant mother interaction and also a sense of being properly cared on behalf of the patient.